Russian energy strategy in the European Union, the former Soviet Union region, and China - Sotiriou, Stylianos A., 1982- (Lexington Books, 2015)
This book examines three bipolar relationships that have emerged as a result of the Eurasian energy triangle Russia-Former Soviet Union region, Russia-EU, and Russia-China and the ways in which they, along with Putin's foreign energy policy, relate to the debate between neorealism and neoliberal institutionalism.